2007
DOI: 10.1128/aac.00072-07
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Nucleotide Sequencing, and Analysis of the AcrAB-TolC Efflux Pump of Enterobacter cloacae and Determination of Its Involvement in Antibiotic Resistance in a Clinical Isolate

Abstract: Enterobacter cloacae is an emerging clinical pathogen that may be responsible for nosocomial infections. Management of these infections is often difficult, owing to the high frequency of strains that are resistant to disinfectants and antimicrobial agents in the clinical setting. Multidrug efflux pumps, especially those belonging to the resistance-nodulation-division family, play a major role as a mechanism of antimicrobial resistance in gram-negative pathogens. In the present study, we cloned and sequenced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 28 publications
4
51
0
1
Order By: Relevance
“…AcrABTolC is a well-characterized multidrug efflux pump of the RND family in E. cloacae (20,26,27). Based on the sequence of the protein AcrB (designated ECL_01233 in ECL13047), the inner membrane transporter protein of the system, we searched for the presence of other members of this family of transporters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AcrABTolC is a well-characterized multidrug efflux pump of the RND family in E. cloacae (20,26,27). Based on the sequence of the protein AcrB (designated ECL_01233 in ECL13047), the inner membrane transporter protein of the system, we searched for the presence of other members of this family of transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence similarities to AcrB varied from 41% to 89%, while amino acid identities were between 23% and 80% ( Table 2). To date, two transporters of a tripartite MDR efflux system have been identified (AcrB and EefB [ECL_00054]) in the genome of the ATCC reference strain (20,28), whereas two others were annotated as belonging to the RND family (ECL_02125 and ECL_02244) (21). ClustalW alignments of all RND-type transporters revealed that three of the five residues corresponding to the amino acids essential for the proton transport within the AcrB identified in E. coli (D407, R970, and T977) were present in all sequences (29,30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of efflux pumps is usually associated with increased MICs of the clinically used aminoglycosides (amikacin, gentamicin, or tobramycin). Examples include efflux pumps belonging to the RND family, such as AcrAB-TolC of E. cloacae (109), AdeABC of A. baumannii (110), or MexXY of P. aeruginosa (105). The impact of efflux pump expression on virulence is described above in the section on ␤-lactams and resistance conferred by efflux pumps.…”
Section: Resistance To Aminoglycosides and Effect On Virulencementioning
confidence: 99%
“…Quando analisaram todos os genes da proteinas da bomba de efluxo acrR, acrA, acrB e tolC, observaram que estas proteinas eram homologas a isolados de E. aerogenes (151,152) .…”
Section: L U I çãO E M Cal Dounclassified